Engaging Students at the Intersections Through Multicultural Centers: An Application of the Culturally Engaging Campus Environment Model. Issue 157 (March 2017) - McShay, James C.
Abstract : The author discusses how Museus' (2014) Culturally Engaging Campus Environment Model (CECE) can be used to re‐envision campus multicultural centers, and programs and services that traditionally employ single‐axis identity interventions when striving to support student growth and success.